INFLUENCE OF OXIDATIVE STRESS AND INFLAMMATION ON THE DEVELOPMENT OF ISCHEMIC HEART DISEASE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - J. L. Lilic; B. Dj. Djindjic; T. K. Kostic; A. J. Jovanovic; D. S. Stanojevic (Российский кардиологический журнал)
Aim. Ischemic heart disease (IHD) is the result of endothelial dysfunction, which is associated with inflammation, increased oxidative stress and hyperglycemia. The aim of our study was to examine the aetiology, importance and intensity of inflammation and oxidative stress in IHD development in patients with diabetes mellitus (DM) type 2.Material and methods. We included 60 male patients with IHD of whom 30 with diabetes type 2. Control group comprised of 12 healthy participants. We analyzed the lipid status, quality of glycemic control (daily glycemia profile — MBG and HbA1c), lipid peroxidation (malondialdehyde-MDA) and inflammation: high sensitivity C reactive protein (hsCRP), intercellular and vascular adhesion molecule-1 (ICAM-1, VCAM-1).Results. Patients with DM type 2 and IHD were obese with higher levels of HbA1c and MBG compared to other two groups. Systolic and diastolic blood pressure, triglycerides, total and LDL cholesterol were significantly higher and HDL was lower in all patients with IHD compared to the control group. CRP levels, ICAM-1, VCAM-1 and MDA were significantly higher in the groups with IHD compared to the control. MDA and VCAM-1 were higher in patients with IHD and type 2 DM than in patients with IHD. There was a significant positive correlation between hsCRP and LDL cholesterol in patients with IHD, regardless of the presence of DM. Significant positive correlation between VCAM-1 and HbA1c values, and between ICAM-1 and hsCRP were shown only in patients with IHD and DM type 2.Conclusion. Inflammation, increased oxidative stress, lipid and metabolic disorders showed significant correlation and have an important pathogenic role in the development of IHD, particularly in patients with DM type 2. Increased levels of hsCRP, VCAM-1 and products of lipid peroxidation are characteristic markers of endothelial inflammation and indicators of the presence of atherosclerotic plaque in patients with DM type 2.